Distribution characteristics, the dissemination and quality of the fine arts and decorative rocks in the centre of Vietnam - Niên, Bùi Ấn; Hòa, Trần Trọng; Anh, Trần Tuấn; Hiếu, Trần Văn; Cẩn, Phạm Ngọc; Hùng, Trần Quốc (Vietnam Journal of Earth Sciences, 2013)
The middle centre of Vietnam had huge potetial of the fine arts and decorative rocks, including magmatic, sedimentary, metamorphic and half precious rocks (jasma, quartz crystal, nazodac).Bioche-limestones have the largest reserves, many colors, beautiful shepes and patterns along with the good-solid distribution. They concentrated in the provinces of Thanh Hoa, Nghe An, Quang Binh and considerabl amount in Quang Tri, Thua Thien-Hue, more rare in Ha Tinh, Quang Nam provinces.Sedimentary rocks of Huu Chanh formations in the Quang Nam have high commercial value. Magmatic rocks exposed with huge mass include: gabbroid, gabbrodiabase, granitoid,… those have colorific, multiform arch-structure distributed mainly in Thanh Hoa, Ha Tinh, Quang Bình, Thua Thien-Hue and Quang Nam provinces. Metamorphic rocks of phase horny and phase green schistic with beautiful structure are olso present with significant quantities distributed more in Quang Tri, Thua Thien-Hue and Da Nang city suburb. There are also semi-precious stones such as jasma and quartz crystal, nazodac in the study area which are distributed on some places in the provinces Thanh Hoa, Nghe An and Ha Tinh.Motst of the above types stones are required to meet the physical and mechanical properties, fine arts for the manufacture and processing of products as well as decorative paving stones. Special variables stones are very large reserves to ensure long term to exploit. The advantage of the distributed stones is near the roads and  easily accessible for exploitation.